A novel enhancement-mode GaN vertical MOSFET with double hetero-junction for threshold voltage modulation. (November 2018) - Zhou, Qi; Wei, Dong; Peng, Xin; Zhu, Ruopu; Dong, Changxu; Huang, Peng; Wei, Pengcheng; Xiong, Wei; Ma, Xiaoyong; Dong, Zhiwen; Yang, Xiu; Chen, Wanjun; et al.
Abstract: A novel Enhancement-mode (E-mode) GaN vertical power MOS transistor (VMOS) with GaN/AlGaN/GaN double heterojunction (DH) is proposed in this work. The polarization effect of the top GaN/AlGaN hetero-junction can be engineered by tailoring the top GaN layer thickness, which enables flexibly modulate the threshold voltage ( V th ) of the DH-VMOS. Meanwhile, the two-dimensional electron gas (2-DEG) at the lower AlGaN/GaN hetero-interface performs as part of the conduction channel of the device which is beneficial for device on-resistance ( R on ) reduction. By increasing the top GaN layer thickness from 5 to 40 nm the V th of the DH-VMOS can be shifted from +2.9 to +4 V. The demonstrated device structure presents a novel and controllable approach to modulate the V th of E-mode GaN vertical power devices, which is of great interests for GaN power device for over kilo-volt applications. Highlights: The proposed device is GaN vertical power MOS transistor with GaN/AlGaN/GaN double heterojunction. The threshold voltage of the proposed device can be flexibly modulated by tailoring the top GaN layer thickness. The 2DEG induced at the lower AlGaN/GaN hetero-interface can reduce overall on-resistance of the device.